Methamphetamine Use and Sexual Risk Behavior among High School Students in Cape Town, South Africa - Plüddemann, A.; Flisher, A.; McKetin, Rebecca; Parry, C.; Lombard, C. (2012)
Objective: To investigate whether methamphetamine use is associated with sexual risk behavior among adolescents. Method: A cross-sectional survey of 1,561 male and female high school students in Cape Town (mean age 14.9 years) was conducted using items from the Problem Oriented Screening Instrument for Teenagers (POSIT) HIV Risk Scale. Results: Nine percent of the students had tried methamphetamine and 30% of male and 17% of female students reported sexual debut. Multinomial logistic regression analyses showed that methamphetamine use in the past year was significantly associated with being in a higher HIV/STI risk category (RRR = 2.1, 95% CI: 1.10-4.03, p & 0.05). Conclusions: Methamphetamine use, coupled with a high HIV prevalence in South Africa, raises serious cause for concern about the potential for methamphetamine to further exacerbate the prevalence and spread of HIV in Cape Town. © 2012 Taylor and Francis Group, LLC.